The Effectiveness of Teaching the Brainstorming Method in Learning the Handball Shooting Skill and Its Impact on Developing Physical Self - Waleed Muhammad Ali Hussein Al-Shahwani (Penerbit Jurnal Indonesia, 2026)
The purpose of the study is to determine how the command approach and the brainstorming method differ when it comes to teaching handball shooting, identifying the level of the physical self among the learners, and identify the differences between the brainstorming method and the command method and its impact on the physical self-development of learners. Given the appropriateness of the research and the nature of the problem, the researcher employed the experimental method. The research sample was specifically chosen from among the 45 students enrolled in the fifth grade of preparatory school at An-Najah School for Boys for Displaced Persons, and the main experimental sample consisted of 30 students, or 67% of the research sample. This sample was then split into two groups, a division (A) for the experimental group and a division (B) for the control group, using the random selection method with a lottery and 15 students for each group. In addition to using physical self-assessment for both the experimental and control groups, this study was carried out during the first half of the academic year (2025/2026). The researcher employed the following statistical means: arithmetic mean, standard deviation, and Levene's test (for homogeneity, percentage, t.test for one sample, t.test for two independent samples